DEVELOPMENT OF GEOMETRIC COMPETENCIES AMONG STUDENTS IN SECONDARY SCHOOLS - Tursunov Ikromjon Gulomjonovich; Narimbetova Zakhia Akhmedovna (Euro Asian Journal Publishing, 2023)
the paper presents the development of scientific and methodological recommendations for the development of geometric competencies of high school students of secondary schools by means of information and communication technologies.
Keywords: technology; STEAM